RESILIENCY OF SMALL-SCALE COMMON CARP (Cyprinus carpio) FARMERS IN WEST PAGADEN RURAL AREA OF SUBANG - WEST JAVA (Daya Lenting Pembudidaya Ikan Mas (Cyprinus carpio) Skala Kecil di Perdesaan Kecamatan Pagaden Barat Subang – Jawa Barat) - Carolina Carolina (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2015)
ABSTRACTSince early 1980s, freshwater fish farming was introduced as an economic activity to the rural community in Subang, West Java Province. Until presently, 5% of the population participate on it, specifically as common carp (Cyprinus carpio) cultivators in freshwater ponds ecosystem. The economic gain from the carp farming triggers vast development indicated by significant landscape conversion from rice fields to fish ponds. Environmental limitation does not seem to become their major concern, because good yields which means good income is their main driving factor to extend and intensify common carp aquaculture. Recognizing the important role of small scale fish farms in West Java common carp production system, we explore their resiliency in confronting challenges encountered in managing the freshwater ecosystem. Utilizing participatory observation and interview, we explore their socio-ecological resilience from the perception of human and nature interaction. The study area is Pagaden Sub District in Subang - West Java. Descriptive analysis is used to articulate the phenomenon enfolded in a socio-ecological framework of thinking. It can be concluded that high dependency to the aquaculture activity, has reached a situation in which ecologically sound technology should be introduced. Included in a scheme of technical assistance which specifically designed to meet the need and in harmony with the socio-cultural characters of small-scale fish farmers, the technology introduction should be carried out to spur the sustainable aquaculture in Subang West Java. This should be a proposed agenda for the local government in support to aquaculture sustainable development.ABSTRAKSejak awal tahun 1980, budidaya ikan air tawar diperkenalkan sebagai kegiatan ekonomi masyarakat desa di wilayah Subang, Propinsi Jawa Barat. Dewasa ini, sekitar 5% populasi terlibat di kegiatan tersebut, terutama sebagai pembudidaya ikan mas (Cyprinus carpio) di ekosistem kolam air tawar. Pendapatan yang diperoleh dari kegiatan budidaya ikan mas telah memicu terjadinya percepatan laju pembangunan yaitu dengan adanya perubahan lansekap dari petak-petak sawah menjadi kolam-kolam ikan. Keterbatasan lingkungan tampaknya tidak dipertimbangkan, karena hasil panen yang tinggi atau keuntungan usaha menjadi tujuan pokok perluasan atau pun intensifikasi kegiatan budidaya ikan mas. Mengingat peran penting pembudidaya ikan skala kecil di rantai produksi ikan mas di Jawa Barat, kami melakukan kajian terhadap daya lenting mereka dalam menghadapi tantangan mengelola ekosistem budidaya ikan air tawar. Dengan memanfaatkan metoda pengamatan-partisipatif dan wawancara mendalam, data dan informasi dari para pelaku budidaya ikan mas skala kecil di Kecamatan Pagaden Kabupaten Subang Jawa Barat ditelusur. Analisis data dilakukan secara deskriptif untuk memberikan ruang artikulatif dalam mengurai fenomena lapangan yang dirangkum dalam kerangka pikir sosio-ekologi. Dapat disimpulkan bahwa meskipun mereka memiliki kearifan lokal tersendiri dalam membudidayakan ikan mas di kolam air tawar, ketergantungan yang tinggi pada kegiatan akuakultur ikan mas, telah sampai pada situasi diperlukannya pengenalan teknologi budidaya yang ramah lingkungan. Pengenalan teknologi tersebut seyogyanya disertai strategi pendampingan yang sesuai dengan kebutuhan dan karakter sosial-budaya para pembudidaya ikan mas skala kecil. Hal ini perlu dijadikan agenda pemerintah daerah untuk diterapkan demi keberlanjutan pengelolaan ekosistem akuakultur di Subang – Jawa Barat.